tính S = 3 -3 ^ 2 + 3 ^ 3 - 3 ^ 4 + ... - 3 ^ 2012
K
Khách
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Những câu hỏi liên quan
T
0
TV
1
13 tháng 1 2017
S=3+3^2+3^3+........3^2012
=> 3S=3^2+3^3+........3^2013
=> 3S-S=2S=(3^2+3^3+........3^2013)-(3+3^2+3^3+........3^2012)
=> 2S=3^2013-3
=> S= \(\frac{3^{2013}-3}{2}\)
NA
0
BH
0
K
1
DB
1
18 tháng 2 2020
3S=3^2-3^3+3^4-3^5+....-3^2013
3S+S=4S=3-3^2013
S=3-3^2013/4
S=3-32+33-34+....-32012
<=> 3S=32-33+34-35+....-32013
<=> 3S+S=(32-33+34-35+....-32013)+(3-32+33-34+....-32012)
<=> 4S=-32013+3
<=> \(S=\frac{-3^{2013}+3}{4}\)
\(S=3-3^2+3^3-3^4+........+-3^{2012}\)
\(\Rightarrow3S=3^2-3^3+3^4-3^5+..........-3^{2013}\)
\(\Rightarrow3S+S=4S=3^{2013}+3\)\(\Rightarrow S=\frac{3^{2013}+3}{4}\)